Tending the valley : a prairie restoration odyssey - D'Alessio, Alice (Wisconsin Historical Society Press, 2020)
"On a gray and drizzly day in 1983, writer Alice D'Alessio and her math professor husband, Laird, made their way down a curving, rutted, tree-lined driveway on their way to a picnic. They were visiting land Laird had inherited from his parents, 115 acres in Wisconsin's unglaciated Driftless Area. Emerging from the trees, Alice had her first glimpse of a patch of land that would become a 25-year labor of love for the couple. In Tending the Valley, she chronicles their efforts to return the land to its prairie state and to manage their oak and pine woods. Along the way they join the movement for land restoration, get involved in a number of landowner and stewardship groups, and discover the depths of dedication required to bring their dream to fruition. D'Alessio shares not only her personal triumphs and setbacks as a prairie steward but also the natural history of the Driftless"--